OP0180 Remission Induction with Dmard Combinations and Glucocorticoids is not Superior to Remission Induction with MTX Monotherapy and Glucocorticoids: Week 52 Results of the High-Risk Group from the Carera Trial. (9th June 2015) - Verschueren, P.; De Cock, D.; Corluy, L.; Joos, R.; Langenaken, C.; Taelman, V.; Raeman, F.; Ravilingien, I.; Vandevyvere, K.; Lenaerts, J.; Geens, E.; Geusens, P.; et al.
Abstract : Background: To date, intensive DMARD combination therapy with glucocorticoids (GCs) is the most effective treatment approach for the management of early Rheumatoid Arthritis (eRA). The ideal content of the combination and the dose of GCs are however not yet known. Objectives: To compare different intensive combination treatment strategies associated with GCs in eRA patients with a poor prognosis at week (W)52 in the CareRA trial. Methods: CareRA is a two year prospective investigator-initiated multicenter RCT rooted in daily practice. DMARD naïve eRA patients were stratified into a high or low-risk group based on classical prognostic markers (presence of erosions, rheumatoid factor, anti-cyclic citrullinated protein and DAS28(CRP). High-risk patients (n=290) were randomized to 1 of 3 treatment strategies. 1) Cobra Classic (n=98): Methotrexate (MTX)+Sulphasalazine+60mg prednisone tapered weekly to 7.5mg daily from W7 2) Cobra Slim (n=98): MTX+30mg prednisone tapered to 5 mg daily from W6 3) Cobra Avant-Garde (n=94):MTX+Leflunomide +30mg prednisone tapered to 5 mg daily from W6 From W28, GCs were tapered in all patients and stopped at W34. A predefined treat to target approach was applied. From W40, we aimed for DMARD monotherapy. Efficacy measures were proportions of DAS28(CRP) remission, good EULAR response, clinically meaningful HAQ response, HAQ=0 (ITT analysis). Radiographic progression was measured via the Sharp Van der Heijde score. Adverse events related to therapy (AEs) were registered. Missing data were imputed by last observation carried forward. Results: Remission rates were 64.3%, 60.2% and 62.8% in the Classic, Slim and Avant-Garde group respectively (p=0.837). Also no other efficacy outcomes did not differ between groups. 82% of X-ray images were available at baseline. Radiographic progression was minimal. SvH scores were 1.3±2.1, 1.3±2.5 and 1.0±1.4 at baseline and changed over 52 weeks 0.3±0.5, 0.4±1.1 and 0.3±0.6 in the Classic, Slim and Avant-Garde group respectively (p=0.581). The total numbers of AEs were 182 in 65 Classic patients, 125 in 64 Slim patients and 174 in 72 Avant-Garde patients (p=0.026). Serious AEs were reported in 3 Classic, 2 Slim and 3 Avant-Garde patients. Conclusions: High rates of remission were achieved at week 52 with csDMARDs and GCs in all remission induction schemes. Cobra Slim showed comparable efficacy with less adverse events compared to DMARD combinations with moderate or high GC dosages. Disclosure of Interest: None declared